1983
DOI: 10.1073/pnas.80.5.1189
|View full text |Cite
|
Sign up to set email alerts
|

Insulin regulation of protein phosphorylation in isolated rat liver nuclear envelopes: potential relationship to mRNA metabolism.

Abstract: The direct addition of insulin to highly purified nuclear envelopes prepared from the livers of diabetic rats resulted in a decrease in the incorporation of 32p into trichloroacetic acid-precipitable proteins. Autoradiography of 32P-labeled envelopes, solubilized in sodium dodecyl sulfate and subjected to electrophoresis, revealed that insulin decreased the phosphorylation of all major protein bands. Insulin produced detectable effects at concentrations between 0.1 and 1 pM, maximal effects at 10 pM, and progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 53 publications
(59 reference statements)
6
23
0
Order By: Relevance
“…For example, isolated nuclei have been shown to respond directly to insulin, resulting in an increase in RNA synthesis (49), protein phosphorylation (50), and transport of macromolecules (51,52). In addition, microinjection of an insulin receptor complex was found to stimulate S6 phosphorylation in vivo without recycling to the plasma membrane (13).…”
Section: Discussionmentioning
confidence: 99%
“…For example, isolated nuclei have been shown to respond directly to insulin, resulting in an increase in RNA synthesis (49), protein phosphorylation (50), and transport of macromolecules (51,52). In addition, microinjection of an insulin receptor complex was found to stimulate S6 phosphorylation in vivo without recycling to the plasma membrane (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is indirect and circumstantial evidence for such a role: (1) plant hormones, whose action is believed to be mediated by Ca 2 *, have been shown to regulate gene expression; 341 -342 - 348 (2) the active form of phytochrome (P /r ), which regulates the expression of a number of genes, can modulate Ca 2 * fluxes in plant cells and organdies;"' (in addition, evidence has been presented by Roux's group for a role of Ca 2 * and calmodulin in phytochrome regulated physiological processes 350 ); and (3) a causal link between the phosphorylation of proteins and the regulation of gene expression has been implicated. 351 Furthermore, phosphorylation of proteins is regulated by Ca 2 *-dependent protein kinases (e.g., Ca 2 *-CaM-dependent protein kinases and protein kinase C). For a better understanding of the molecular mechanisms by which Ca 2 * acts, it is essential that the possible role of Ca 2 * in gene regulation be studied.…”
Section: Calcium and Gene Expressionmentioning
confidence: 99%
“…Several laboratories have demonstrated that extracellular insulin affects nuclear processes including mRNA efflux (1), protooncogene expression (2), transcription of tyrosine aminotransferase (3) and phosphoenolpyruvate carboxykinase (4) genes, cell growth (5), and phosphate incorporation into the nuclear envelope (6) and nuclear lamins (7). The first step leading to these effects is the binding of insulin to receptors in the plasma membrane.…”
mentioning
confidence: 99%